Fibroadipogenic progenitors: a potential target for preventing breast muscle myopathies in broilers - Jung, Usuk; Kim, Minjeong; Voy, Brynn H. (Frontiers in Physiology, 2024)
Genetic selection for high growth rate, breast muscle yield, and feed efficiency in modern broilers has been a double-edged sword. While it has resulted in marked benefits in production, it has also introduced widespread incidence of breast muscle myopathies. Broiler myopathies are phenotypically characterized by myodegeneration and fibrofatty infiltration, which compromise meat quality. These lesions resemble those of various myopathies found in humans, such as Duchenne muscular dystrophy, Limb-girdle muscular dystrophy, and sarcopenia. Fibroadipogenic progenitors (FAPs) are interstitial muscle-resident mesenchymal stem cells that are named because of their ability to differentiate into both fibroblasts and adipocytes. This cell population has clearly been established to play a role in the development and progression of myopathies in mice and humans. Gene expression studies of wooden breast and other related disorders have implicated FAPs in broilers, but to our knowledge this cell population have not been characterized in chickens. In this review, we summarize the evidence that FAPs may be a novel, new target for interventions that reduce the incidence and development of chicken breast muscle myopathies.